Debate Strategies in Early Modern Dialogue - Heitsch, Dorothea B. (Erasmus studies, 2015)
In Jean Bodin’s Colloquium Heptaplomeres seven interlocutors come together in the house of Paulus Coronaeus in Venice. They represent seven different faiths and world views: Catholicism, Lutheranism, Calvinism, Judaism, Islam, Deism or Naturalism, and a syncretic faith tied to philosophical skepticism. The meeting’s participants all debate religion and even whether such debate should be allowed. Bodin develops the character of Octavius Fagnola, the former Catholic converted to Islam, according to a wealth of sources including an Islamic debate tradition that is known as munāẓara. The role of Octavius has important implications for the meaning of Bodin’s work as well as for Renaissance dialogue in general.